Broadband optical wavelength conversion through four-wave mixing in W3-type AlGaAs photonic crystal waveguides. (22nd February 2023) - Oda, Hisaya; Hosokawa, Youhei; Hayashi, Kazuki; Ozaki, Nobuhiko; Ikeda, Naoki; Sugimoto, Yoshimasa
Abstract: We realized a wide-band wavelength conversion method through four-wave mixing in W3-type AlGaAs photonic crystal waveguides. AlGaAs exhibits a large third-order nonlinearity. Furthermore, because of its large bandgap, two-photon absorption can be avoided in the 1550 nm range. A four-wave mixing efficiency of −7 dB was obtained for a pump peak power of 7 W. Furthermore, by utilizing the two even guided bands of the W3-type photonic crystal waveguide, a conversion bandwidth greater than 38 nm was achieved with a conversion efficiency of −22 dB.